Cluster Analysis and Network Visualization of Biology Education Research in Indonesia: A Bibliometric Analysis - Noviansyah Kusmahardhika; Susriyati Mahanal; Balqis Balqis; Haidir Algi Gaffar Faridha (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
This study aims to explore the development of BER in Indonesia from 2014-2023 on the Scopus database. Current studies illustrate that the number of publications on biology education has increased in recent years. This trend is likely to continue, as evidenced by the increasing number of publications. A total of 253 papers from the Scopus database were analyzed using VOSviewer software. These findings reveal that BER in Indonesia has grown rapidly in recent years. Zubaidah is the most prolific author, and Universitas Negeri Malang is a leading institution in the progress of BER. The most studied research topics in the last three years are education computing, learning systems, learning processes, and e-learning. The learning topics are plants (botany), animals, biotechnology, and genetics. We also highlight that many topics still get less attention, such as technology-based learning in biochemistry, algae, and protists. We hope this study can illustrate the current status of BER, so that it can help to map the direction of future research in Indonesia.